Effect of kinaesthetic differentiation of the in-run position on jump length in Polish national ski jumpers - Wilk, M.; Gebala, L.; Gepfert, M.; Drozd, M.; Kostrzewa, M.; Piwowar, R.; Mroszczyk, W.; Zajac, A. (Baltic Journal of Health and Physical Activity, 2018)
Background: The aim of study was to evaluate the effect of kinaesthetic differentiation during the in-run position on the in-run speed and jump length in ski-jumping team.